Internal and External Environment Analysis in Improving the Performance of Teachers of Muhammadiyah Junior High School 35 Sigambal, South Rantau District, Labuhanbatu Regency - Rafly Prahmana Hidayat; Rusydi Ananda; Makmur Syukri (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the influence of work motivation, teacher competence, school culture, and principal's leadership on teacher performance at SMP Muhammadiyah 35 Sigambal. Teacher performance is a key factor in determining the quality of learning and educational success. This study uses a quantitative approach with a survey method of 13 active teachers as respondents. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression with the help of SPSS. The results of the partial test showed that the variables of work motivation and teacher competence did not have a significant effect on teacher performance, while school culture and principal leadership had a positive and significant effect. However, simultaneously, these four variables had a significant effect on teacher performance with a Fcal value of 69.912 and a significance of 0.000 (0.05). The determination coefficient (R²) of 0.918 indicates that 91.8% of the variation in teacher performance can be explained by all four independent variables in the model. These findings confirm the importance of synergy between internal (motivation and competence) and external factors (school culture and leadership) in forming a work environment conducive to improving teacher performance. This study recommends strengthening school culture and leadership quality as priority strategies in improving the quality of education.